اسلام کا تصور اجماع اطلاقات و مستدلات : Consensus on the Concept of Islam: Applications and Arguments - Abrar Hussain; Dr. Hafiz Muhammad Abrar Awan; Ms. Tooba Khalid (International Research Journal of Arabic and Islamic Studies, 2024)
The concept of Islam embodies a consensus among its adherents, encapsulating a holistic worldview, spiritual practice, and ethical framework. This consensus is grounded in the Quran, the primary scripture of Islam, and the teachings of the Prophet Muhammad. Key aspects include monotheism, submission to the will of Allah, and the Five Pillars: declaration of faith, prayer, fasting, charity, and pilgrimage. The application of Islamic principles extends beyond individual rituals to encompass societal ethics, governance, and interpersonal conduct. Islamic jurisprudence, derived from the Quran and Hadith, provides a framework for interpreting and applying these principles to contemporary issues. The consensus on Islam is sustained through continuous interpretation and adaptation, ensuring relevance across diverse cultures and contexts. Keywords: Islam, consensus, Quran, Prophet Muhammad, monotheism, Five Pillars, Islamic jurisprudence, ethics, governance.